How CSR is conducted in Zambia. What drivers, issues and processes are used? An Analysis of the Lusaka Stock Exchange (LSE) companies. - Garg, Sumeet R. (2013)
The notion corporate social responsibility developed from the western world is a new concept in Zambia. Researchers have suggested that the concept of CSR can make positive contributions to companies operating in African and developing countries as it has done in western countries. This research study aims to offer how companies listed in the Lusaka Stock Exchange (LSE) market in Zambia use CSR. Frameworks used in CSR will used to investigate this research with the main focus on institutional theory (IT). The research will evaluate CSR in Zambia by seeing which IT pressures (normative, regulative and cultural-cognitive) are adopted by Zambian companies. The study relies on secondary data done from web content analysis of websites of each company listed in the LSE as well as literature surrounding the adoption of CSR in the Zambian context. The findings from this research reveal that there are various types of CSR present in Zambian companies. Different institutional pressures encourage different companies. Specifically, normative and culture-cognitive pressures, where as, regulatory pressures by the government are very minimal. Companies all focus on different issues and processes. However there is isomorphism between companies leading to companies taking similar approaches of CSR. Zambian companies mainly focus on philanthropic CSR, which is mainly giving back to the society. This is very different in western countries as suggested by Carroll (1991) where priority is given to economic and legal responsibilities while philanthropic are given the least. So CSR in Zambia is developed to suit the needs of the community, hence, companies implement CSR activities accordingly. This research recommends that government needs to introduce regulations to companies in order to practice effective CSR the same recommendation given by Gilberts (2008) research on CSR in Kenya.